Two Cheers for Anarchism : Six Easy Pieces on Autonomy, Dignity, and Meaningful Work and Play. - Scott, James C. (Princeton University Press, 2012)
James Scott taught us what's wrong with seeing like a state. Now, in his most accessible and personal book to date, the acclaimed social scientist makes the case for seeing like an anarchist. Inspired by the core anarchist faith in the possibilities of voluntary cooperation without hierarchy, Two Cheers for Anarchism is an engaging, high-spirited, and often very funny defense of an anarchist way of seeing--one that provides a unique and powerful perspective on everything from everyday social and political interactions to mass protests and revolutions. Through a wide-ranging series of.